Analysis of the nutritional and fatty acid profile of sacha inchi tempe (Plukenetia volubilis L.) using different cooking methods - Diana Nur Afifah; Diana Nur Afifah; Daniaty Afifatus Salam; Fitria Nugraheni; Nina Resti; Rachma Purwanti; Gemala Anjani; Mursid Tri Susilo; Nuryanto; Made Astawan; Irma Sarita Rahmawati (Frontiers in Nutrition)
BackgroundIndonesia is experiencing food insecurity regarding soybean products. To address this challenge, sacha inchi (Plukenetia volubilis. L) has been identified as a potential raw material for making tempe due to the high levels of protein and polyunsaturated fatty acid (PUFA).ObjectiveThis research aimed to determine the potential of sacha inchi bean tempe on proximate content, PUFA, and the effect of different cooking methods.MethodWater and ash content were analyzed using the gravimetric method. Moreover, protein, fat, carbohydrates, and fatty acid were evaluated using the Kjeldahl, Soxhlet, difference, and Gas Chromatography (GC) method.ResultsThere were significant differences (p ≤ 0.05) in water content, ash content, protein, saturated fat, unsaturated, and PUFA in fermentation time. Fermentation increased protein (19.50–20.50%) while reducing water (30.26–28.51%) and PUFA (35.35–32.99%). Cooking methods significantly impacted fatty acids, with steaming retaining the highest PUFA (29.97%) and linolenic acid (14.63%), while frying increased saturated fat (11.24%).ConclusionFermentation process in sacha inchi bean tempe could reduce the water content and saturated fat. This process also increased the ash, protein, and monounsaturated fat content, while the best cooking method was found to be steaming.